Computational optimization of housing complexes forms to enhance energy efficiency - Derazgisou, SeyedAli; Bausys, Romualdas; Fayaz, Rima (Journal of Civil Engineering and Management, 2018)
This study aimed to consider the field of energy saving in architectural design utilizing computer analysis and calculation. In this analysis, architecture design with an approach to optimizing energy consumption in the design of individual units, complex plan sites, and apartment sets using a computer was studied. Parameters affecting this research include the geometry of units, the arrangement and location relationship of buildings, and the form and height of apartment units. Different plans were produced by utilizing the initial plan of the designer and changing some aspects of it approved by the architectural design using the parametric modeling technique. Utilizing similar logic and a shift in the arrangement of buildings on the site, a variety of options were produced. By selecting existing and pre-designed plans, the optimal form was produced by computer. After computer-simulating each option, the energy analysis process was started for each building design. In the optimization process for each of the three designs, a genetic algorithm was used to achieve the optimal solution. After accomplishing the various stages of optimization, the final option compared with the initial design had reductions in energy consumption of 21% in plan design, 2% in site plan design, and 26% in apartment units form design. It should be noted that the processes of simulation and optimization were performed in the context of a continuous algorithm and by utilizing parametric tools that reduced the duration of this process.